The Effect Of Employee Training And Development On Work Productivity At CV. Sasana Citra Mandiri - Saputra, Aldi; Aryanti, Rahmi; Ermelia, Sri (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of employee training and development on work productivity at CV. Sasana Citra Mandiri. The methods used in this study include validity, reliability, multicollinearity, simultaneous test (F), partial test (t), multiple linear regression, and determination coefficient test (R²). The results of the study indicate that training and development simultaneously have a very strong and significant effect on work productivity, with a contribution of 97.9%, while the remaining 2.1% is influenced by other variables such as compensation and incentives and time and workload management. Partially, training has a greater effect than development on increasing productivity. With a correlation coefficient value of 0.99 and an adjusted R Square of 0.978, it can be concluded that employee training and development have a crucial role in driving work productivity in this company.